Use of the Earth Remote Sensing Data to assess the state of recreational forests in the Kokshetau National Park - Murzagulova, Z.A.; Karnaukhova, T.V.; Fakhrudenova, I.B.; Tazitdinova, R.M. (Fundamental and Experimental Biology, 2022)
Currently, modern satellite systems are increasingly used in various areas of studying natural resources and the dynamics of natural phenomena, and in carrying out an ecological assessment of the state of the environment. At the same time, remote sensing data provide greater visibility, data acquisition in dynamics, high speed of image acquisition, and transmission. The article presents the results of spatio-temporal changes in the vegetation biomass of the Kokshetau National Park based on the calculation and analysis of the vegetation index. Based on the analysis of the NDVI values, the tendencies of changes in phytomass were estimated and correlations with the main climatic characteristics of the territory for the studied period were revealed. For the research, we used Landsat satellite images and geoinformation mapping in the ArcGIS software package. In general, there is a negative trend in the values of the indices for theforests of all functional zones over a 10-year period. For the preservation and further renewal of forests, the National Park of Kokshetau needs to carry out a number of regulatory measures.